RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH PADA PEMBERIAN PUPUK KANDANG DAN PUPUK ANORGANIK - Pantas Simanjuntak; Parsaoran Sihombing; Toni Aprianto Sijabat (Majalah Ilmiah METHODA, 2020)
Shallot (Allium ascalonicum) is one of the potential horticulture plant to be developed. In most parts of the world shallot has become a popular spice that makes food tasty in addition to its much needed nutrients. Goat manure and NPK ferilizers are used to get more plant production The study was conducted to investgate the respon sof growth and production of shallot on the application of goat manure and anorganic fertilizerNPK. The experiment was a Randomized Block Design replicated three times with twelve tretments. The goat manure rates (K) consisted of four levels, i.e K0 (nogoatmanureapplication), K1 (1 kg plot-1), K2 (2 kg. plot-1), K3 (3kg.plot-1), while the NPK fertilizer consisted of three levels, i.e N1 (10g.plot-1), N2 (15g.plot-1), N3 (20g.plot-1), The result indicated the application of goat manure up to K3(3 kg.plot-1)affected plant height,nuber of leaves, ,bulb fresh weight bulb dryweight, and bulb diameter significantly. Increasing NPK application up to level 20g.plot1, significantly affected plant height, bulb fresh weight, bulb dry weight, bulb diameter but not significantly affected plant height, leaves number